Rule of Financial Market Success to Growth Gross Domestic Products (Global Journal of Management and Business Research, 2014)
This search concentrates on rule of financial market success to growth domestic products which solve problems of increasing general budget deficit and increasing financial market dealing weakness. Searcher found that balancing between producers' fair return and supporters covering needs is the rule. Investors locally and internationally as shareholders, creditors, government, employee and customers can support producing locally in case products covers their different needs with suitable cost but success of supporting producer by financial market is limit as result to seller developing tools to transfer loss, government policies which affect on demand and supply and ignorance causing to get unusual return by speculations or to get other return as result to monopolize information to be costly. Searcher recommended balancing between powers welfares up to rule of financial market success to growth gross domestic products which help to solve depression.
Keywords: depression; financial market; gross domestic products; supporters and ignorance